Triangular nexus between foreign direct investment, international tourism, and energy consumption in the Chinese economy: accounting for environmental quality - Udemba, Edmund Ntom (Springer Heidelberg, 2019)
Recently, China is named among the most carbon dioxide (CO2)-emitting countries in the world after the United State of America (USA). A major part of Chinese carbon dioxide emissions is as a result of offshore industrial activities which come into the economy as foreign direct investment (FDI). Following this, the present study seeks to investigate the nexus between CO2 emissions, FDI, energy use, and tourism arrivals, and possibly to advise on who will bear the responsibility of offshore CO2 emissions. Utilizing ARDL-bound testing and Granger causality approaches for both short- and long-run effects the author found that economic growth (GDP) has a positive relationship with both tourism arrivals, energy use, FDI, and CO2.This contributes to heavy CO2 emissions which the author classified as the outsourced/offshore CO(2)emissions in China's FDI. Tourism arrivals have a bi-directional (feedback) causal relationship with energy use and a uni-directional causal relationship with CO2(transmitting from tourism to CO2). Both FDI and energy use have a bi-directional (feedback) causal relationship; CO2, energy use, and tourism arrivals have a unidirectional relationship with GDP which established the triangular nexus causality among the variables and the impact on GDP. Hence, the policy implication should be geared towards implementing the policies and regulations that will checkmate and reduce the excesses of foreign firms to the environment quality of China and promote environmentally friendly economic activities.
Keywords: CO2 emissions; Energy use; FDI; Tourism arrivals; Offshore activities; Economic growth; China